HUBUNGAN DUKUNGAN KELUARGA TERHA HUBUNGAN DUKUNGAN KELUARGA TERHADAP PERILAKU REMAJA PUTERI TENTANG PERUBAHAN FISIK PADA MASA PUBERTAS DI SMP NEGERI 1 DELI TUA TAHUN 2020 - Mona Fitri Gurusinga (Jurnal Penelitian Keperawatan Medik, 2020)
Teenagers, who are studying at Junior High Schools, are in their puberty. In general, teenagers undergo various problems and difficulties in adjusting themselves to their environment in their puberty. The objective of the research was to find out the correlation between family support and female teenagers behavior in their physical change in their puberty at SMP Negeri 1 Deli Tua tahun 2020. The research used an analytic method with cross sectional design. It was conducted in September 2014 to February 2015. The population was 137 grade VII female students of SMP Negeri 1 Deli Tua tahun 2020and 68 of them were used as the samples. The data were analyzed by using chi square test and multiple logistic regression analysis. The result of the research showed that there was the correlation of emotional (p=0.004), information support (p=0.000), and instrumental support (p=0.002) with the behavior (knowledge, attitude, and action) of female teenagers in their puberty. The variable of information support had the most dominant correlation with the female teenagers behavior at Exp (B) of 5.591. It is recommended that the management of the school provide more knowledge and information about the puberty period for their students, especially female students by upgrading them periodically in the knowledge of reproduction health. It is also recommended that parents discuss with their daughters about the change toward puberty and guide them in digging up information about puberty without any fear so that they can be familiar in their daily activities.